Services & Resources / Wolfram Forums
-----
 /
MathGroup Archive
2007
*January
*February
*March
*April
*May
*June
*July
*August
*September
*October
*Archive Index
*Ask about this page
*Print this page
*Give us feedback
*Sign up for the Wolfram Insider

MathGroup Archive 2007

[Date Index] [Thread Index] [Author Index]

Search the Archive

Enquirey

  • To: mathgroup at smc.vnet.net
  • Subject: [mg74778] Enquirey
  • From: "Rita Ray" <rayrita1 at gmail.com>
  • Date: Thu, 5 Apr 2007 04:06:09 -0400 (EDT)

I am trying to solve two equation with two unknowns. I am using
Mathematica 5.2.  Below is my program


Solve[{a*Exp[2*w]-a^2*Exp[w+(x-y)*z]+a^2*Exp[w-(x-y)*z]-a*Exp[w+(x-y)*z]-a*=
Exp[w-(x-y)*z]+a^2*Exp[2*(x-y)]+a-a^2+a^2*x*Exp[w+(x-y)*z]
+a^2*x*Exp[w-(x-y)*z]-a*x*Exp[w+(x-y)*z]-a*x*Exp[w-(x-y)*z]+2*a*x-2*a^2*x-(=
(a^3*w*Exp[w+(x-y)*z])/z)-((a^3*w*Exp[w-(x-y)*z])/z)+((a^2*w*Exp[w+(x-y)*z]=
)/z)+((a^2*w*Exp[w-(x-y)*z])/z)-((2*a^2*w)/z)+((2*a^3*w)/z)====0,-((a*Exp[-=
w+(x-y)*z]*z*(-((1-a)*w)-2*w*a^2+2*w*a^3+a^2*w*Exp[w-(x-y)*z]-a^3*w*Exp[w-(=
x-y)*z]+a^2*w*Exp[w+(x-y)*z]-a^3*w*Exp[w+(x-y)*z]+a*z-a^2*z+a*z*Exp[2*w]+a^=
2*z*Exp[2*(x-y)]-a*z*Exp[w-(x-y)*z]+a^2*z*Exp[w-(x-y)*z]-a*z*Exp[w+(x-y)*z]=
-a^2*z*Exp[w+(x-y)*z]+2*a*x*z-2*a^2*x*z-a*x*z*Exp[w-(x-y)*z]+a^2*x*z*Exp[w-=
(x-y)*z]-a*x*z*Exp[w+(x-y)*z]+a^2*x*z*Exp[w+(x-y)*z]))/(a*Exp[-w+(x-y)*z]+(=
1-a)*Exp[-w-(x-y)*z]))-(a*Exp[-w+(x-y)*z]*((1-a)*z*Exp[-w-(x-y)*z]-a*z*Exp[=
-w+(x-y)*z])*(-((1-a)*w)-2*w*a^2+2*w*a^3+a^2*w*Exp[w-(x-y)*z]-a^3*w*Exp[w-(=
x-y)*z]+a^2*w*Exp[w+(x-y)*z]-a^3*w*Exp[w+(x-y)*z]+a*z-a^2*z+a*z*Exp[2*w]+a^=
2*z*Exp[2*(x-y)]-a*z*Exp[w-(x-y)*z]+a^2*z*Exp[w-(x-y)*z]-a*z*Exp[w+(x-y)*z]=
-a^2*z*Exp[w+(x-y)*z]+2*a*x*z-2*a^2*x*z-a*x*z*Exp[w-(x-y)*z]+a^2*x*z*Exp[w-=
(x-y)*z]-a*x*z*Exp[w+(x-y)*z]+a^2*x*z*Exp[w+(x-y)*z]))/(a*Exp[-w+(x-y)*z]+(=
1-a)*Exp[-w-(x-y)*z])^2+(a*Exp[-w+(x-y)*z]*(-2*a^2*z*Exp[2*(x-y)]+a^2*w*z*E=
xp[w-(x-y)*z]-a^3*w*z*Exp[w-(x-y)*z]-a^2*w*z*Exp[w+(x-y)*z]+a^3*w*z*Exp[w+(=
x-y)*z]-a*z^2*Exp[w-(x-y)*z]+a^2*z^2*Exp[w-(x-y)*z]+a*z^2*Exp[w+(x-y)*z]+a^=
2*z^2*Exp[w+(x-y)*z]-a*x*z^2*Exp[w-(x-y)*z]+a^2*x*z^2*Exp[w-(x-y)*z]
+a*x*z^2*Exp[w+(x-y)*z]-a^2*x*z^2*Exp[w+(x-y)*z]))/(a*Exp[-w+(x-y)*z]+(1-a)=
*Exp[-w-(x-y)*z])====0},{x,y}]


Thank you.

Rita Ray.

Ph.D. student


  • Prev by Date: Re: N function problematic performance (V. 5.2)
  • Next by Date: Re: verification
  • Previous by thread: Re: question
  • Next by thread: Re: Enquirey